COMPARATIVE ANALYSIS OF ELECTORAL SYSTEM IN DEMOCRACIES WORLDWIDE - Yasmeen Naz (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Electoral systems significantly shape political representation, governance, and democratic outcomes. They are categorized into majoritarian, proportional representation (PR), and mixed systems. Majoritarian systems like First-Past-the-Post (FPTP) offer stability but often underrepresent smaller parties. PR systems ensure inclusive representation but can lead to fragmented parliaments and coalition governments. Mixed systems combine both, balancing stability with broader representation. Comparative analysis reveals trade-offs between stability, inclusivity, and governance effectiveness, with PR promoting gender equality and minority representation, while majoritarian systems enhance direct voter-representative relationships. Regional trends show North America’s use of FPTP, Europe’s preference for PR, and Asia and the Pacific’s growing adoption of mixed systems. Africa and Latin America use PR to address fragmentation and instability.FPTP systems, used in the UK, Canada, and India, produce clear outcomes but often result in disproportionate representation. PR systems in Sweden and South Africa provide equitable representation but cause legislative fragmentation. Mixed systems like Germany’s Mixed Member Proportional (MMP) balance local representation and proportionality. Ireland’s Single Transferable Vote (STV) promotes proportionality but is complex. Both India and the US face underrepresentation of smaller parties despite using FPTP. A tailored approach is needed for fair governance, with future research focusing on electoral reforms and their effects on political polarization and inclusivity.